Eye Superior Service Development Strategy to Increase Competitiveness at Purbowangi Kebumen Hospital - Ratnawati, Yeni; Pertiwi, Arlette Suzy Puspa; Veranita, Mira (CV. Civiliza Publishing, 2025)
This study aims to analyze the strategic steps taken by RSU Purbowangi in improving the effectiveness of eye superior services, identify obstacles and efforts to improve accessibility and quality of services, and evaluate the strategies applied in service development to remain competitive. The approach used in this research is qualitative with a descriptive method, which allows in-depth exploration of the strategy for developing superior services. Data were obtained through interviews with ophthalmologists, nurses, and hospital management, and analyzed using data reduction techniques, data presentation, and conclusion drawing. The results showed that RSU Purbowangi implemented a strategy to increase the effectiveness of the eye service by strengthening human resources through specialist training, applying the latest medical technology, and optimizing the service management system to increase efficiency and reduce medical errors. The main obstacles faced include limited facilities and high patient demand, which are overcome by improving the queuing system, adding specialist medical personnel, and optimizing technology in services. To maintain competitiveness, the hospital implemented service innovations, such as online consultations, as well as increased collaboration with eye specialist clinics and conducted comparative studies to adopt best practices in health services.